Parenting stress, resilience, religiosity, and emotional competence in caregivers of children with special needs - Desiningrum, Dinie Ratri; Hermawati, Donna; Somantri, Maman; Karim, Chamilul Hikam Al (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Children with special needs require caregivers to care for them and provide full or partial assistance in the carrying out of their daily activities, including undergoing therapy, going to school, receiving medication, and performing their daily routines. This can cause stress and a burden of care for caregiver, meaning that caregivers require emotional competence; this study aims to develop a model of such competence. Using a cross-sectional, correlational quantitative approach, data were collected from 120 caregivers selected purposively from the Yamet Foundation in Central Java. The research instruments were the Profile of Emotional Competence, Centrality of Religiosity Scale, Resilience Scale, and the Parenting Stress Scale. The data were analyzed using structural equation modeling (SEM) with Lisrel. The findings reveal that the proposed model successfully captures the relationships between parenting stress, resilience, religiosity, and emotional competence. Parenting stress significantly and negatively affects emotional competence, with a path coefficient of β = -.39, t = -5.29, with higher stress levels correlating to reduced resilience and religiosity. In addition, resilience and religiosity act as mediator variables, with a score of z = -2.346 for religiosity and z = -2.017 for resilience, meaning that both variables act as mediators. However, resilience and religiosity do not directly influence each other. The study suggests that enhancing parents’ resilience and religiosity may buffer the impact of parenting stress on emotional competence. Thus, psychosocial support programs should integrate resilience-building and spiritual-based approaches to empower families of children with special needs.